Sargassum fusiforme fucoidan alleviates diet-induced insulin resistance by inhibiting colon-derived ceramide biosynthesis. Issue 18 (10th August 2021) - Zhang, Ya; Liu, Jian; Mao, Genxiang; Zuo, Jihui; Li, Shijun; Yang, Yue; Thring, Ronald W.; Wu, Mingjiang; Tong, Haibin
Abstract : Sargassum fusiforme fucoidan (SFF) remodels gut microbiota, enhances TUDCA content, inhibits the biosynthesis of colon-derived ceramide by blocking FXR signaling, restoring insulin sensitivity in DIO mice. Abstract : Sargassum fusiforme fucoidan (SFF) is a highly sulfated heteropolysaccharide with various biological activities. As one of the causative factors of type 2 diabetes mellitus (T2DM), insulin resistance has become a global health issue. In this study, we investigated the potential pharmacological mechanisms by which SFF ameliorates insulin resistance in high-fat diet (HFD)-fed mice. SFF significantly enhanced tauroursodeoxycholic acid (TUDCA, a conjugated bile acid) levels and inhibited the farnesoid X receptor (FXR) signaling in the colon. SFF administration reduced ceramide levels in both serum and colonic tissue of HFD-fed mice, as well as reduced expression of SPT and CerS genes, which encode enzymes crucial to the biosynthesis of ceramides regulated by FXR signaling. Pearson's analysis showed that the TUDCA level was positively correlated with the gut bacteria Clostridium, and this was further validated in pseudo-germfree mice. Taken together, the results suggested that SFF increased TUDCA levels by remodeling gut microbiota, and TUDCA, a natural FXR antagonist, inhibited the FXR/SHP signaling pathway to reduce colon-derived biosynthesis of ceramide, thereby improving insulin resistance in the diet-induced obese (DIO) mice. This study has provided new insights into the therapeutic potential of S. fusiforme fucoidan in metabolic diseases.